Individual and stable autoantibody repertoires in healthy individuals. (2nd January 2019) - Neiman, Maja; Hellström, Cecilia; Just, David; Mattsson, Cecilia; Fagerberg, Linn; Schuppe-Koistinen, Ina; Gummesson, Anders; Bergström, Göran; Kallioniemi, Olli; Achour, Adnane; Sallinen, Riitta; Uhlén, Mathias; et al.
Abstract: In the era towards precision medicine, we here present the individual specific autoantibody signatures of 193 healthy individuals. The self-reactive IgG signatures are stable over time in a way that each individual profile is recognized in longitudinal sampling. The IgG autoantibody reactivity towards an antigen array comprising 335 protein fragments, representing 204 human proteins with potential relevance to autoimmune disorders, was measured in longitudinal plasma samples from 193 healthy individuals. This analysis resulted in unique autoantibody barcodes for each individual that were maintained over one year's time. The reactivity profiles, or signatures, are person specific in regards to the number of reactivities and antigen specificity. Two independent data sets were consistent in that each healthy individual displayed reactivity towards 0–16 antigens, with a median of six. Subsequently, four selected individuals were profiled on in-house produced high-density protein arrays containing 23, 000 protein fragments representing 14, 000 unique protein coding genes. Based on a unique, broad and deep longitudinal profiling of autoantibody reactivities, our results demonstrate a unique autoreactive profile in each analyzed healthy individual. The need and interest for broad-ranged and high-resolution molecular profiling of healthy individuals is rising. We have here generated and assessed an initial perspective on the global distribution of the self-reactive IgG repertoire in healthy individuals, by investigating 193 well-characterized healthy individuals. Highlights: A unique longitudinal profiling of autoantibody repertoires in healthy individuals Autoantibody profiles are highly individual and stable over time All individuals display IgG binding to human protein fragments The specificity of disease associated autoantigens needs to be thoroughly characterized The identification of a small set of highly reactive autoantigens Importance of stringent antigen and sample specific cut-offs for defining reactivity